Action of exogenous ascorbic acid on physiological quality of cowpea seeds artificially aged - Brilhante, Jean Carlos de Araújo; Oliveira, Alexandre Bosco de; Silva, José Wendney Lima e; Enéas Filho, Joaquim (Semina: Ciências Agrárias, 2013)
The aim of this study was to evaluate the effects of pre-treatment and post-treatment with ascorbic acid in reducing the damage caused by aging in cowpea seeds, which were aged in artificial accelerated aging chamber (45Â°C, 99% relative humidity in the dark) for 72 h and it were subjected to four treatments: T1 - non-aged seeds were not treated with ascorbic acid (AsA); T2 - non-aged seeds treated with AsA; T3 - seeds before aging were subjected to a treatment with AsA to 0.85 mM; T4 - seeds after aging were subjected to a treatment with a 0.85 mM AsA. The aging of seeds for 72 h (T2) caused significant damage in the cell membranes of cowpea seeds, as evidenced by a increase in electrolyte leakage, higher level of lipid peroxidation and a lower germination percentage, when compared with the control (T1). T4 results were like the control treatment, with a lower electrolyte leakage and lipid peroxidation, well as a higher germination percentage, when compared with T2. The exogenous application of 0.85 mM ascorbic acid in cowpea seeds after artificial aging can mitigate its detrimental effects on the membranes integrity and seed physiological quality.